Deconstructing the Outsider Puzzle: The Legitimation Journey of Novelty - Cattani, Gino; Ferriani, Simone; Lanza, Andrea (Organization Science, 2017)
The proposition that outsiders often are crucial carriers of novelty into an established institutional field has received wide empirical support. But an equally compelling proposition points to the following puzzle: the very same conditions that enhance outsiders’ ability to make novel contributions also hinder their ability to carry them out. We seek to address this puzzle by examining the contextual circumstances that affect the legitimation of novelty originating from a noncertified outsider that challenged the status quo in an established institutional field. Our research case material is John Harrison’s introduction of a new mechanical method for measuring longitude at sea—the marine chronometer—which challenged the dominant astronomical approach. We find that whether an outsider’s new offer gains or is denied legitimacy is influenced by (1) the outsider’s agency to further a new offer, (2) the existence of multiple audiences with different dispositions toward this offer, and (3) the occurrence of an exogenous jolt that helps create a more receptive social space. We organize these insights into a multilevel conceptual framework that builds on previous work but attributes a more decisive role to the interplay between endogenous and exogenous variables in shaping a field’s shifting receptiveness to novelty. The framework exposes the interdependencies between the micro-, meso-, and macro-level processes that jointly affect an outsider’s efforts to introduce novelty into an existing field. The e-companion is available at https://doi.org/10.1287/orsc.2017.1161 .